Bonneville Salt Flats: This place. (1st March 2015) - Worden, Jessica
Utilizing multiple narratives to move in and out of a critical reading of Among the Salt Flats, a performance score written by the author in 2014, this article explores the different modes by which a performance writing practice generates multiplicities of place. The disruptive characteristics of performance jar the perceived fixed temporalities and locations of writing. These disruptions in the time and place of writing invite new proximities to the page which in turn recuperate the distance of representation. This article rewrites the disrupted linguistic geographies of Among the Salt Flats, focussing on the destabilizing force of this form on linearity and represents it through a text that moves between critical writing, image and first-person narrative.We drive out to the Bonneville Salt Flats in my brother's car. I sit in the passenger's seat and we talk; I never learned how to drive. I look out the window at the flat-lying desert, endless and uniform in tone, shape and texture. The air outside parches the earth. From inside the car, I lick at the cracks in my lip that resemble the only breaks in the monotony of the ground. As we come closer to our destination, the landscape transforms into frozen greyish rifts and waves. We take the car out over the crust, park and proceed on foot past the warning signs.